Seismic reliability assessment of ageing integral bridges - Ní Choine, Mairéad (Trinity College (Dublin, Ireland). Department of Civil, Structural and Environmental Engineering, 2014)
This thesis carries out a tune dependent seismic risk assessment of ageing integral bridges as well as providing a comparison between the seismic performance of integral and jointed bridges.
Keywords: Civil, Structural and Environmental Engineering, Ph.D.; Ph.D. Trinity College Dublin